Find an explicit rule for the nth term of the sequence.

1, 3, 9, 27, ...
an = 1 • 3n + 1
an = 3 • 1n - 1
an = 1 • 3n - 1
an = 1 • 3n

Respuesta :

hello ;
an = 1 • 3n - 1

Answer:

Option C is the correct answer.

Step-by-step explanation:

1, 3, 9, 27, ...

This is an example of Geometric progression.

First term, a  = 1

Common ratio, r = 3

We have n th term of GP

            [tex]a_n=ar^{n-1}[/tex]

Substituting

            [tex]a_n=ar^{n-1}=1\times 3^{n-1}[/tex]

Option C is the correct answer.          

ACCESS MORE